Deconstructing the ESG black box: A systematic review of risk heterogeneity, measurement noise, and financial stability - Dewi Pangestuti; Subur Subur (Akuntansiku, 2026)
This review synthesizes research on the understanding of sustainability risks in the financial sector, focusing on three key components of sustainability risk: environmental, social, and governance (ESG). Although the integration of ESG in finance is becoming increasingly important, the primary challenges are risk heterogeneity and measurement inconsistencies. This study aims to develop a taxonomy of sustainability risks, evaluate their impact on financial stability and investment decisions, and identify best practices in ESG-based risk management. To achieve this, the review examines 60 empirical, qualitative, and conceptual studies published between 2000 and 2025, focusing on the banking sector and emerging markets. A variety of methodologies are employed, including econometric analysis, artificial intelligence (AI), and case studies. The findings indicate that environmental and governance risks have a significant impact on financial stability, while social risks still require more accurate measurement. ESG integration has proven to enhance risk mitigation, though challenges remain regarding data quality, regulatory fragmentation, and inconsistent metrics. The use of AI technology and agile methods can improve risk assessment accuracy and adaptability. The study also finds that sustainability crisis management is more focused on risk anticipation rather than reactive responses to crises. The practical implications of these findings highlight the need for a coordinated ESG risk management framework, as well as further research on the role of technology and crisis response strategies in strengthening sustainable financial stability.